Are Students Motivated Enough?: A Study of Students’ Motivation in Online English Course - Adhi Nurhartanto; Tyas Desita Wengrum; Widya Rahmawati (IJLHE: International Journal of Language, Humanities, and Education, 2023)
It is still debatable whether distance learning is effective to be implemented fully. In pandemic where classes have been conducted online for more than a year, students’ motivation in attending the lectures fully is questionable. This study aims to determine students’ motivation in attending the lectures gradually. The students’ motivation six months after the face-to-face meeting was forbidden is compared to their motivation a year after the classes were done online. This research is a quantitative study using a quasi-experimental research design with a time-series model. The population of this research is all 1st and 2nd semester students who took English For Business 1 and 2 courses. Data collection was carried out by using questionnaires to gain students’ motivation using Dornyei’s L2MSS questionnaires and additional 10 items from regular face to face class modified into items about the online language learning added to Language Learning section. Data analysis was conducted using the t test for paired samples. The results of the analysis obtained that distance learning is effective to maintain students’ motivation in attending classes in shorter period while it possibly decreases in longer time and teacher possibly needs creativity to maintain the students’ motivation.